Providing Students With Severe Disabilities Access to the General Education Curriculum. (September 2016) - Olson, Amy; Leko, Melinda M.; Roberts, Carly A.
This case study explored how multiple educational personnel in a middle school identified as an exemplar of inclusive education defined and provided students with severe disabilities access to the general education curriculum. Data sources including a questionnaire, interviews, observations, observation reflections, and artifacts were collected from 12 participants who worked as administrators, general education teachers, special education teachers, or paraprofessionals. Findings point to educational personnel who are committed to providing access to the general education curriculum in general education classrooms and carry out this mission through shared responsibility, collaboration, peer supports, and multi-faceted learning structures. These findings are discussed in relation to future research and practice in the areas of inclusion and severe disabilities.